State-dependent pricing and its implications for monetary policy - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2019)
Strong evidence now exists both in macro and micro data that price/wage durations are depent on the state of the economy and especially inflation. We embed this dependence in a macro model of the US that otherwise does well in matching the economy's behaviour in the last three decades; it now also matches it over the whole post-war period. This finding implies a major role for monetary policy in influencing the economy's price stickiness. We find that by targetin nominal GDP monetary policy can achieve high price stability while also preventing large cyclical output fluctuations.
Keywords: E2; E3; 330; state-dependence; New Keynesian; Rational Expectations crises; price stability; nominal GDP